A Shape Memory Acrylamide/DNA Hydrogel Exhibiting Switchable Dual pH‐Responsiveness. (19th October 2015) - Hu, Yuwei; Lu, Chun‐Hua; Guo, Weiwei; Aleman‐Garcia, Miguel Angel; Ren, Jiangtao; Willner, Itamar
Abstract : Shape memory acrylamide/DNA hydrogels include two different crosslinkers as stabilizing elements. The triggered dissociation of one of the crosslinking elements transforms the shaped hydrogel into an arbitrarily shaped (or shapeless) quasi‐liquid state. The remaining crosslinking element, present in the quasi‐liquid, provides an internal memory that restores the original shaped hydrogel upon the stimulus‐triggered regeneration of the second crosslinking element. Two pH‐sensitive shape memory hydrogels, forming Hoogsten‐type triplex DNA structures, are described. In one system, the shaped hydrogel is stabilized at pH = 7.0 by two different duplex crosslinkers, and the transition of the hydrogel into the shapeless quasi‐liquid proceeds at pH = 5.0 by separating one of the crosslinking units into a protonated cytosine–guanine–cytosine (C–G·C + ) triplex. The second shaped hydrogel is stabilized at pH = 7.0, by cooperative duplex and thymine–adenine–thymine triplex (T–A·T) bridges. At pH = 10.0, the triplex units separate, leading to the dissociation of the hydrogel into the quasi‐liquid state. The cyclic, pH‐stimulated transitions of the two systems between shaped hydrogels and shapeless states are demonstrated. Integrating the two hydrogels into a shaped "two‐arrowhead" hybrid structure allows the pH‐stimulated cyclic transitions of addressable domains of the hybrid between shaped and quasi‐liquid states. Abstract : A shape memory acrylamide/DNA hydrogel exhibiting dual switchable pH‐responsiveness is presented. The hybrid hydrogel exists at pH = 7.0 in a "two‐arrowhead" structure. One domain is transformed into a quasi‐liquid shapeless state at pH = 5.0, whereas the second domain transforms into the quasi‐liquid state at pH = 10.0. The transformation of the quasi‐liquid to shaped hydrogels is reversible due to internal memory elements.